When Policy Is Not Enough: Intimate Partner Violence Survivors’ Search for Housing Assistance in Washington, D.C - Cattaneo, Lauren B. (Violence against women, 2025)
Policies throughout the U.S. respond to the well-documented relationship between housing instability and intimate partner violence (IPV), but in practice survivors’ needs often remain unmet. In this community-based participatory study, an interdisciplinary research team interviewed 41 survivors seeking emergency housing assistance at the sole public gateway for homeless families in Washington, D.C. Only four survivors received immediate assistance, and half were determined ineligible for services. While some felt genuinely supported, many survivors faced long wait times and experienced shaming and demoralizing treatment that exacerbated their risk. We discuss the influence of contextual factors including discriminatory narratives surrounding who deserves help, and a lack of system resources driving a scarcity mindset. Recommendations include a sustained, critical, and collaborative approach to evaluating local implementation of ostensibly supportive policies.